Masculinidade em anúncio(s): recepção publicitária e identidade de gênero - Santos, Filipe Bordinhão dos (2012)
This research proposes a reception study over masculinity representations in Brazilian advertisements transmitted over free-to-air television and its role in distinct class men's gender identity formation. We did align to the Cultural Studies strand, especially, to Jesús Martín-Barbero's Latin American theoretical and methodological mediation perspectives. Still in theoretical terms we do emphasize on the discussions referring to male gender's social construction and, in a complementary way, on the articulation with the contemporary notion of social class. Methodologically, we did perform a reception study with 10 different age, civil state and profession men, who do reside in Santa Maria, classified as high and popular classes by Quadros and Antunes' definition (2001). The data collection techniques used in this study were the questionnaire, which consisted of a pilot study with 40 instruments, and a semi structured in depth interview. Besides that, for the reception exam over the masculine gender we did mark out a corpus of advertisements (beer, car, technology, bank and clothing/hygiene products) defined by the results of the questionnaires and used as responsible support to stimulate debate with the receptors. We did analyze the mediations of sociality, rituality and tecnicity (MARTÍN-BARBERO, 2006) in the advertising speech's appropriation relations (negotiation or resistance) concerning to the masculinity representations, defined by beauty, sexuality, work and family categories. As a result of this work, the advertising shows up as an important source of patterns and references to contemporary subjects to live the masculinity; at the same way contributing to the relativization of the traditional masculine pattern, related to machism and patriarchy that hegemonically vigorates until a few decades ago. At last, the construction of gender identities based on beauty, sexuality, work and family, from the readings and the ways of using the advertising speech is made in a differenced way by the cleavages of social classes.